Analisis implementasi gerakan literasi sekolah (gls) di sekolah dasar ditinjau dari social learning theory - Luluk Anjani Rahmawati; Karsono Karsono (Universitas Sebelas Maret, 2025)
This study aims to analyze the implementation of the School Literacy Movement (GLS) at SDN Kemasan 1 Surakarta from the perspective of Albert Bandura's social learning theory. The approach used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The informants in this study consisted of the school principal, literacy coordinator, classroom teachers, and students from lower and upper grades, with a total of 5 respondents selected through purposive sampling. Data validity was tested using source and technique triangulation to ensure the validity and credibility of the findings. The results of the study indicate that literacy activities in this school have been effective and reflect the four main aspects of social learning theory: attention, memory, reproduction, and motivation. Students demonstrate high attention through varied literacy methods, information retention through meaningful activities, the ability to reproduce behavior through practical application, and enhanced motivation through teacher reinforcement. This research implies that social learning theory can serve as a theoretical framework for designing social interaction-based literacy programs that not only build cognitive skills but also the character of students. Practically, these results can be used as a basis for developing literacy strategies by teachers and social-based literacy policies by schools.